Do good unto all : Charity and poor relief across Christian Europe, 1400-1800 - Thomley, Jared B.; Fehler, Timothy G. (Book collections on Project MUSE., 2023)
This volume explores the ideas, institutions, and experiences that shaped Catholic, Lutheran, Calvinist, and Anabaptist charity in early modern Europe.